Новые виды настоящих молей (Lepidoptera, Tineidae, Myrmecozelinae) — степных детритофагов - Загуляев, А.К. (Вестник зоологии, 1972)
Five new species of the genus Myrmecozela Z l l are described: М. kasachstanica, М. stepicola, М. saule, М. imeretica, М. asariella. Caterpillars of these moths аrе steppe detritophages and only some of them settle in bumble-bee nests as well as in formicaria and termitaria.